Exploitable ambiguities & the unruliness of natural resource dependence: Public infrastructure in North Dakota's Bakken shale formation - Smith, Kristin K.; Haggerty, Julia H. (Journal of rural studies, 2020)
Whether public infrastructure investments reinforce or disrupt natural resource dependence constitutes a critical knowledge gap in resource geography and energy impacts scholarship. This research revitalizes William Freudenburg's (1992) addictive economies framework to address the conundrums and ambiguities of infrastructure in communities that host unconventional oil and gas (UOG) development. The addictive economies framework is applied to a large regional water supply project in North Dakota (the Bakken Formation) to investigate the endogenous and exogenous drivers that shape infrastructure decisions. The analysis illustrates how a descriptive approach to theorizing dependence foregrounds geographic context, allowing for a more nuanced understanding of the everyday challenges facing decision-makers in communities with extractive industries. Specifically, it illustrates how infrastructure embodies exploitable ambiguities that can be leveraged by different stakeholders to justify and advance diverging agendas. The principal findings suggest that the interplay between the UOG industry and the local geography shapes governance decisions related to public infrastructure with ambiguous future consequences for communities. •Booms in unconventional oil and gas often prompt parallel booms in infrastructure.•The long-term impacts of public infrastructure investments are ambiguous.•Infrastructure's unruliness can be exploited by different stakeholders.•Long-term debt from infrastructure can clash with short-term industry decisions.•A descriptive approach to resource dependence highlights boomtown challenges.